The physicality of the other masks from the ancient Near East and the Eastern Mediterranean - The Physicality of the Other - Masks as a Means of Encounter 2015 Leipzig; Berlejung, Angelika 1961-; Filitz, Judith E. 1984- (Tübingen Mohr Siebeck, 2021)
Cover -- Title -- Table of Contents -- Preface -- Abbreviations -- I. Introductory Considerations -- JUDITH E. FILITZ - Of Masks and Men. Thoughts on Masks from Different Perspectives -- ALFRED SCHÄFER - Zwischenwelten. Maskenauftritte im Egungu/Kutito-Geheimbund -- II. Masks in Egypt -- RENÉE F. FRIEDMAN - Masking in Early Egypt. A View from Hierakonpolis -- ALEXANDRA VON LIEVEN - Can Deities Be Impersonated? The Question of Use of Masks in Ancient Egyptian Rituals -- ASJA MÜLLER - Masking the Dead in Roman Egypt -- III. Masks in the Southern Levant -- IZAK CORNELIUS - The "Face of Death" and the "Face of Baal"? Masks from the Stone Age and Bronze Age -- ITZHAQ SHAI - Two Late Bronze Age Ceramic Masks from Tel Burna, Israel -- ANGELIKA BERLEJUNG - Masks in the Old Testament? Masks in Ancient Palestine/Israel! -- EPHRAIM STERN - Iron Age-Persian Masks and Protomes from Tel Dor -- IV. Masks in Syria and Mesopotamia -- JULIANE STEIN - Spätbronzezeitliche Masken aus Nordsyrien -- CLAUDIA BEUGER - Maskerade im 1. Jt. v. Chr. in Mesopotamien -- TAKAYOSHI OSHIMA - The King's Godly Image as the Perfect Physiognomy of the Holder of the Kingship. Royal Ideology in the Neo-Assyrian Period -- V. Masks on Their Way to Europe -- ADRIANO ORSINGHER - Ritualized Faces. The Masks of the Phoenicians -- ERIN WALCEK AVERETT - Playing the Part. Masks and Ritual Performance in Rural Sanctuaries in Iron Age Cyprus -- ANGELIKI VARAKIS - Encountering the Heroic prosopeion in Fifth Century Theatre Performance -- DANIEL DOST - ‚Quid sibi personae volunt?' Erkundungen im Schnittfeld von lateinisch persona und etruskisch phersu -- VI. Appendix: Katalog/Catalogue.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Konferenzschrift -- 2015 -- Leipzig